2022
DOI: 10.1101/2022.04.27.489705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EGFR inhibition led ROCK activation enhances desmosome assembly and cohesion in cardiomyocytes

Abstract: The epidermal growth factor receptor (EGFR) is a ubiquitously expressed receptor tyrosine kinase, which is dysregulated in several kinds of cancer and heart diseases. Arrhythmogenic cardiomyopathy (AC) is a familial heart disease in part caused by impaired desmosome turnover. Thus, stabilization of desmosome integrity, may provide potential new treatment options. Desmosomes, apart from cellular cohesion, provide the structural framework of a signaling hub. Here, we investigated the role of EGFR inhibition on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(143 reference statements)
0
1
1
Order By: Relevance
“…Furthermore, increased levels of EGF, indicating an increased EGFR activity, also increased the protein levels of ADAM17 ( Santiago-Josefat et al, 2007 ). However, in our Jup −/− mice, which express low levels of DSG2 and high levels of EGFR ( Shoykhet et al, 2022 ), ADAM17 protein levels were not significantly increased. It has been suggested that the proteolytic activity of ADAM17 is not regulated by protein levels, but by posttranslational modifications ( Dusterhoft et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, increased levels of EGF, indicating an increased EGFR activity, also increased the protein levels of ADAM17 ( Santiago-Josefat et al, 2007 ). However, in our Jup −/− mice, which express low levels of DSG2 and high levels of EGFR ( Shoykhet et al, 2022 ), ADAM17 protein levels were not significantly increased. It has been suggested that the proteolytic activity of ADAM17 is not regulated by protein levels, but by posttranslational modifications ( Dusterhoft et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 59%
“…Upon knockdown of Adam17 using siRNA or application of the ADAM17 inhibitor for 24 h, we did not observe a change in cellular cohesion as compared to siNT (non-target) or vehicle treated HL-1 cardiomyocytes, respectively ( Figures 2B, C ). Since ADAM17 can transactivate the EGFR by EGF shedding, and EGFR inhibition can also lead to positive adhesiotropy ( Shoykhet et al, 2022 ), we assessed whether the TAPI-1-induced positive adhesiotropy requires EGFR. However, we did not observe changes in EGFR signaling ( Supplementary Figures 2C–F ).…”
Section: Resultsmentioning
confidence: 99%